BioNanoScience - Carrara, Sandro; Erokhin, Victor; Buehler, Markus; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
BioNanoScience is a new field of research that has emerged at the interface of nanoscience and biology, aimed at integration of nano-materials into engineered systems, for new applications in biology and medicine. The aim of BioNanoScience is to provide a forum for the rapidly growing area of bionanoscience, emphasizing the link between structure, properties and processes of nanoscale phenomena in biological and bioinspired structures and materials for a variety of engineered systems. The journal promotes fundamental research in bionanoscience and engineering to advance nanoscience, nanotechnology and engineering, toward application in biology and medicine. This new journal will provide a forum for this interdisciplinary community by publishing highest quality peer-reviewed publications. Methods covered in this journal include experimental (including but not limited to imaging, via SEM/AFM/optical microscopy and tweezers; x-ray scattering and diffraction tools, electrical/magnetic characterizations; design, and synthesis via self-assembly, layer-by-layer, Langmuir films; biotechnology, via recombinant DNA methods, and protein engineering, etc.), theoretical (e.g. statistical mechanics, nanomechanics, quantum mechanics, etc.) and computational (bottom-up multi-scale simulation, first principles methods, supercomputing, etc.) research. Areas of applications of interest include all relevant physical, chemical, and biological phenomena and their engineering into integrated systems: mechanical (e.g. deformation, adhesion, failure), electrical and electronic (e.g. electromechanical stimulation, capacitors, energy storage, batteries), optical (e.g. absorption, luminescence, photochemistry), thermal (e.g. thermomutability, thermal management), biological (e.g. how cells interact with nanomaterials, molecular flaws and defects, biosensing, biological mechanisms s.a. mechanosensing), nanoscience of disease (e.g. genetic disease, cancer, organ/tissue failure), as well as information science (e.g. DNA computing). The journal covers fundamental structural and mechanistic analyses of biological processes at nanoscale and their translation into synthetic applications. Studies of interfaces (e.g. between dissimilar structures, organic-inorganic) are of particular interest. In the area of interface between dissimilar structures, papers are also welcome on hybrid systems, including CMOS integrated circuits embedding organic nanostructures as well as biological components.
Keywords: Biophysics; Biological physics; Electronic circuits; Biomaterials; Nanotechnology; Circuits and Systems; Biological and Medical Physics, Biophysics; Nanotechnology; Biomaterials